Knowledge, attitude, and practice toward COVID-19 among Iraqi people: a web-based cross-sectional study - Ali Jadoo, Saad Ahmed; Alhusseiny, Adil Hassan; Yaseen, Shukur Mahmood; Al-Samarrai, Mustafa Ali Mustafa; Al-Rawi, Ru’ya Abdulhadi; Al-Delaimy, Ahmed K.; Abed, Mohammed Waheeb; Hassooni, Hanan Raheem (Journal of Ideas in Health, 2020)
Background: Iraq was among the first countries invaded by the novel human coronavirus (SARS-COV-2) after China. This study aimed to assess the Iraqi people's knowledge, attitudes, and practices toward COVID-19 during the pandemic. Methods: A cross-sectional study recruiting an online self-reported survey conducted from 17-31 July 2020. Data of 877 participants have undergone descriptive, univariate, and multivariable regression analyses, respectively, to assess the differences in mean scores and identify factors associated with knowledge, attitudes, and practices (KAP) toward COVID-19. Results: Most of the respondents (78.8%) from the urban region, highly educated (69.7%), aged less than 45 years (61.2%), females (58.3%), married (51.9%), and 74.0% self-ranked health as good. Less than half (45.4%) were employed; however, the average monthly income was USD 400 or more in about 66.8% of them. The mean knowledge, attitude and practice score was 15.57 ± 2.46 (range: 0-20), 38.88 (SD = 3.57, (range: 11-55), and 5.13 (SD = 1.14, range: 0–6), respectively. Findings of regression analysis showed that higher educated (p< 0.001), urban residents (P <0.001), employed (P =0.040), and having an income level of USD 400 or more (P <0.001) were significantly associated with upper knowledge score. Female gender and employed respondents are significantly associated with positive attitude scores, but inversely respondents with an income of USD 400 or more are significantly associated with a negative attitude. Regarding practice score, the female gender and those living in an urban region had better practice, but the young age group (0-44 years) was significantly associated with the weak practice. Conclusion: Although Iraq has adopted a preventive and precautionary plan to control the spread of coronavirus. However, the public's knowledge and attitude toward COVID-19, coupled with the unstable political and security situation, have greatly affected the commitment to preventive measures.